Tematski geslovnik slovenščine za nadaljevalce - Slaninová, Darina; Pirih Svetina, Nataša, 1970-; Masarykova univerzita. Ústav slavistiky (2006)
Tematický heslář slovinštiny pro pokročilé: užitečná příručka pro všechny, kdo chtějí mluvit více slovinsky.
A Word Boook of Slovene for Intermediates: helpful manual for all who want to speak more Slovenian. You can choose from 14 themes. The advantage is that you can choose a theme in which you are inetersted the most and it is not necessary to go from the beginning chapter by chapter.
Vedoucí práce: Nataša Pirih Svetina
Diplomová práce (Mgr.)--Masarykova univerzita, Filozofická fakulta, 2006
Keywords: slovinština; konverzace; Slovenian language; conversation, terms and phrases; diplomové práce; master's theses